Shaped by Booms and Busts: How the Economy Impacts CEO Careers and Management Styles - Schoar, Antoinette; Zuo, Luo (Review of Financial Studies, 2017)
We show that economic conditions when managers enter the labor market have long-run effects on their career paths and managerial styles. Managers who began their careers during recessions become CEOs more quickly, but at smaller firms. They also have more conservative styles, such as lower investment in capital expenditures and research and development, more cost cutting, and lower leverage and working capital needs. These recession effects appear to be largely driven by the characteristics of the CEO's first job (recession CEOs tend to start in smaller or private firms), which suggests that the early work environment is important to the formation and selection of managers.